A novel approach for brazing MgF2 ceramic to TA15 alloy using AgCu/GH4169/Bi2O3B2O3ZnO composite braze fillers - Liangbo Sun; Yue Wen; Tao Liu; Chunfeng Liu; Tipeng Shan; Xinghong Zhang; Jie Zhang (Journal of Materiomics)
A two-step brazing process was successfully employed to join MgF2 ceramic and TA15 alloy using eutectic Ag28% (in mass fraction) Cu alloy and Bi2O3B2O3ZnO (BBZ) glass as fillers, by introducing a 100 μm thick GH4169 interlayer. Multiscale characterization revealed that interdiffusion and reaction occurred at the joint interfaces. As a result, a reliable joint system consisting of TA15/TiCu/TiCu2Al/Ag(s,s) + Cu(s,s)/TiCu2Al/TiCuNi + Ag-rich layer/GH4169/nano-oxide layer/glass/Mg3(BO3)F3+MgO + MgF2 reaction layer/MgF2 was formed. The GH4169-interlayer exhibited adaptive compatibility though its interaction with AgCu and BBZ glass fillers, effectively accommodating strong interface bonding and thermal mismatch stress between TA15 and MgF2 substrates. It shows an excellent shear strength (32 MPa, at room temperature) as well as thermal cycling stability without any cracking or spallation observed after the 20 thermal shock cycles between room temperature and 300 °C. It provides valuable insights into designing highly reliable ceramic/metal joints that demonstrate superior stability and adaptability in specific applications.